A prospective double‐blind cross‐sectional study of the accuracy of the use of dry vaginal tampons for self‐sampling of human papillomaviruses. (4th August 2014) - Khan, AM; Sasieni, P; Singer, A
<x xml:space="preserve">Abstract</x> Objective To evaluate if a dry vaginal tampon can be used to accurately detect high‐risk human papillomaviruses (HPV) and so be used as a cervical screening tool for the early detection of high‐grade cervical intraepithelial neoplasia (CIN2+). Design Prospective double‐blinded cross‐sectional study. Setting Colposcopy unit in North London. Population Women referred for colposcopy with both abnormal and normal cervical cytology were invited to participate in this study. Methods Women inserted a dry tampon in the vagina before colposcopic examination. Polymerase chain reaction (PCR) HPV test was carried out on the dry tampon. Cervical samples were collected by the colposcopist for HPV testing using Hybrid Capture (an HC2 kit). Main outcome measure Detection of CIN2+. Results In all, 501 women participated in the study. The majority of participants (69%) were in the 25–35‐year age group. Overall sensitivity and specificity for detection of CIN2+ by vaginal tampon were 76% (95% confidence interval [95% CI] 65–85) and 61% (95% CI 56–66), respectively, and HC2 had a sensitivity of 92% (95% CI 83–97) with a specificity of only 46% (95% CI 41–51). Sensitivity ratio was 0.83 (95% CI 0.73–0.94) (P = 0.004) and Specificity ratio for CIN2+ was 1.33 (95% CI 1.22–1.45). Indicating that the tampon test was significantly (P < 0.0001) more specific. Sensitivity decreased and specificity improved with increasing age. Conclusions Dry tampon test showed reasonably high sensitivity and specificity when detecting CIN2+. The majority of participants (98%) approved of the use of dry tampons as a method of sample collection, which could be an effective alternative method for detecting HPV infection.